2012
DOI: 10.5102/ucs.v10i1.1623
|View full text |Cite
|
Sign up to set email alerts
|

<b>Violência contra adolescentes grávidas: uma revisão integrativa</b> - doi: 10.5102/ucs.v10i1.1623

Abstract: Violência contra adolescentes grávidas: uma revisão integrativa* Violence against pregnant teenagers: a review Resumo Objetivou-se apontar características do contexto que envolve a violência contra adolescentes grávidas, por meio de uma revisão bibliográfi ca. Para tanto, a partir da utilização dos descritores "violência" e "gravidez na adolescência", selecionaram-se doze estudos pertencentes às bases de dados ME-DLINE, LILACS e ADOLEC com abrangência temporal entre os anos 1998 e 2010. As adolescentes são mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Muitas vezes a gestação na juventude é inicialmente vista como um acontecimento problemá-tico, gerador de frustrações e insegurança para muitas jovens e suas famílias, mas, para algumas, traduz o produto do desejo de ser mãe 4 . De forma contrária, quando não há a aceitação da gravidez pelos indivíduos que convivem com a jovem, torna-se comum a violência intrafamiliar, não só de caráter físico, mas também psicológico, social e emocional, podendo levar ao abandono ou à imposição do abortamento sob condições muitas vezes precárias 5,6 .…”
Section: Introductionunclassified
“…Muitas vezes a gestação na juventude é inicialmente vista como um acontecimento problemá-tico, gerador de frustrações e insegurança para muitas jovens e suas famílias, mas, para algumas, traduz o produto do desejo de ser mãe 4 . De forma contrária, quando não há a aceitação da gravidez pelos indivíduos que convivem com a jovem, torna-se comum a violência intrafamiliar, não só de caráter físico, mas também psicológico, social e emocional, podendo levar ao abandono ou à imposição do abortamento sob condições muitas vezes precárias 5,6 .…”
Section: Introductionunclassified
“…Being a victim of constant oppression, the young woman may become isolated, which reduces her support network. 4,16 Research conducted in São Paulo with pregnant adolescents concluded that 47.5% of the participants suffered psychological violence perpetrated mainly by their parents. This factor enabled for adolescents to associate pregnancy with a bad event that would have harmful consequences for their future and their intra-family relationships, causing them psychological distress.…”
Section: Went To See the Doctor 'There' He Said Like This: This Gimentioning
confidence: 99%
“…1,2 However, reactions to early pregnancy may be contradictory to overlap feelings of surprise, sadness, anger and even acceptance and joy. 3 Pregnant adolescents do not always receive the expected support since when they discover their daughters' pregnancies some parents are mainly responsible for aggressions both by physical means and by ridicule and humiliation 4 . The negative family feelings are related to the fact that the birth of a child interferes significantly in the well-being and the future perspective of these young people since it is closely linked to other problems, such as the high rates of school abandonment, leading to entry into the labor market and worsening socio-economic conditions.…”
mentioning
confidence: 99%